German interest in studing the conditions of Palestine in the nineteenth century (1830-1860) (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Arts Humanities Series, 2025)
German participated in the treaty of London in 1840, which was concluded to resolve the eastern question. Since that date, Germany's policy changed and it began to move towards the Arab east with several policies, including evangelism, which was one the ways Germany penetrated the Arab east in general and Palestine in particular. This policy formed a map for starting a wave of political and economic interventions in Palestine, The beginning was the convergence of Prussian-British interests and the establishment of the evangelical archbishopric of Jerusalem, then the beginning of the formation of German colonies in Palestine, such as the German temple society ,which sought to implement its plans to settle Jews in Palestine and convert them to Christianity in preparation for the formation of the kingdom of god that they intended to establish in Palestine.